Home automation: knowledge about the existence and importance of its use by people with physical disabilities - wheelchair users in Redenção - PA, Brazil (Research, Society and Development, 2022)
Automation, a set of technologies with the ability to program events in an environment, in order to make the operation of various equipment automatic, through integrated systems and internet connection. This research aimed to demonstrate knowledge about the existence, use, and importance of use by people with physical disabilities - wheelchair users. It was possible to observe that 36.6% of the people who answered the questionnaire said they did not know how "voice command" is used in home automation projects, in addition to 33.3% of the participants claiming not to know or even to have heard talking about “smart home”, however, the “legality” of the statements was perceived, when 87.9% said they knew that several segments and types of residential control such as: cameras, locks, smart lamps and sockets, air conditioning, universal, can be controlled by voice command, a fact that demonstrates that the integration of automation tools is not yet strongly known as the general concept. It was concluded that the participants have general knowledge about what automation is, a more succinct perception of home automation, unaware of the way in which smart homes are defined and technically designed and believe that home automation can contribute by facilitating the day-to-day life of people with physical disabilities or reduced mobility.